The effect of perceived autonomy support from the coach and ego- and task- involvement upon ego and task environments in junior elite ice hockey - Jakobsen, A. M. (LASE Journal of Sport Science, 2021)
Based on the self-determination and achievement goal theory, we have investigated the effect of autonomy support from the coach and task-oriented and ego-oriented athletes on a task versus an ego environment. We expected a positive relationship between perceived autonomy support from the coach together with task involvement from the athletes on a task environment. Furthermore, we expected a negative relationship between task environment and ego-involved athletes and a negative relationship between perceived autonomy support from the coach and an ego environment. Among ego-involved athletes we expected a positive relationship with an ego environment and a negative relationship between task-involved athletes and an ego environment. Participants consisted of 401 young Norwegian ice hockey players aged 14 - 18 years. We used three different questionnaires to measure perceived coach autonomy support, task- and ego-orientation in sport and perceived motivational climate in sport. We conducted two regression analyses, one with task environment and one with ego environment as the dependent variable. The independent variables were perceived autonomy support from the coach and task- and ego-involvement. We conclude that a task environment derives from perceived autonomy support from the coach and task-oriented athletes. An ego-oriented environment, on the other han, is created when there is a lack of autonomy support from the coach and ego-involved athletes.